Assessing the Effectiveness of the Tuberculosis Control Program at Kedaton Health Center, Bandar Lampung City - Dian Utama Pratiwi Putri; Hernida Hernida; Mella Tri Andani; Nabillah Dwi Affrianti; Muhammad Ali Satria; Safa Liana (Health Dynamics, 2025)
Background: Tuberculosis (TB) is one of the infectious diseases that has become a global health challenge, including in Indonesia. This study aims to analyze the TB control program at the Kedaton Health Center, Bandar Lampung City, using the Input-Process-Output approach. Methods: The data used consisted of primary data, such as in-depth interviews and observations, as well as secondary data from the TB program achievement report for the last three years (2022–2024). Results: The results of the analysis show significant fluctuations in the achievement of the target, with case detection coverage decreasing from 91.76% in 2023 to 40.78% in 2024. The main inhibiting factors include limited human resources, low public awareness, lack of supporting facilities, and suboptimal program management structure. Health workers who concurrently work and the number of tracking cadres is minimal, reducing the effectiveness of case tracking. In addition, social stigma against TB is an obstacle in early detection and treatment. Conclusion: To overcome this obstacle, it is recommended to strengthen human resources, optimize facilities such as transportation and diagnostic tools, and improve public education through a community-based approach. The implementation of this strategy is expected to increase the effectiveness of the TB program at the Kedaton Health Center, support the achievement of national targets, and contribute to global efforts to reduce the burden of TB disease.